THE ROLE OF PROFITABILITY IN MEDIATING CAPITAL STRUCTURE, AND FIRM SIZE ON FIRM VALUE MEDIATED BY PROFITABILITY - Sajiwo Tri Prakoso; Diana Pramudya Wardhani; Nur Amalina; Civi Erikawati; Chandra Wisnu Utomo (International Journal of Social Science, 2022)
This study aims to examine the effect of capital structure and firm size on profitability and firm value. The total population and sample are 32 real estate property companies listed on the Indonesia Stock Exchange. The data is taken from secondary data listed on the IDX from the financial statements of www.idx.com. The data analysis technique in this study used multiple regression analysis and was expanded with path analysis. From the results of regression testing, it can be concluded as follows: Capital structure has a negative and significant effect on profitability, while firm size has a positive and significant effect on profitability. Partially, capital structure and profitability have a positive and significant effect on firm value, while firm size has a negative and insignificant effect. Profitability has a positive and significant effect on firm value. Profitability as an intervening variable does not mediate the relationship between capital structure and firm size with firm value shown from t arithmetic which is smaller than t table Sobel test.